"Development and Application of FBBFBEM Solution for 3-D Complex- Shaped Domain". (2018) - Anand, S.N.; Sreerama Reddy, T.V.; Madhu, D.; Rao, T.K.
Abstract: In this article, for solving the 3-D thermal conduction problem an effort has been by using the boundary integral equation formulation and BEM. Multidimensional non uniform bodies which are in complex shape are addressed by triangular patch modeling method. The arbitrary geometry of the body is divided into elements which are of triangular patches by triangulation algorithm. A numerical solution is developed by defining the basis functions on the face of the triangles generated in the triangular patch modeling, in contrast to defining it on the nodes as followed in the regular mesh generation technique like BEM, FVM and FEM solutions. The temperature distribution from the surface of the hot body is plotted for understanding the nature of its behaviors. Also the convergence study is conducted to get the solution convergence towards the exact solution for the case of a sphere. Other geometries like cube, cylinder and cone are also treated and analyzed for the field variable.